2021
DOI: 10.1002/adts.202100121
|View full text |Cite
|
Sign up to set email alerts
|

Efficient 2T CsKPb(IBr)3—Tin Incorporated Narrow Bandgap Perovskite Tandem Solar Cells: A Numerical Study with Current Matching Conditions

Abstract: This study numerically investigates a highly efficient tandem‐structured CsKPb(IBr)3−FACsPbSnI3,FAMASnGeI3, andMAPbSnI3, perovskite‐perovskite model solar cells using the solar cell simulator capacitance software (SCAPS−1D), consisting of wide‐bandgap top potassium incorporated inorganic cesium‐based perovskite cell (CsKPb(IBr)3−1.92eV) and narrow‐bandgap bottom tin incorporated perovskite cells (FACsPbSnI3−1.29eV,FAMASnGeI3−1.40eV,and MAPbSnI3−1.16eV). The study explores and optimizes the front and rear perov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…† First, the top cell was simulated by adopting the AM 1.5 spectrum with a conventional temperature of 300 K, known as a standalone condition, using drift-diffusion SCAPS-1D software. 60 The simulated solar cell showed an excellent PCE of 9.05% in combination with J sc = 11.42 mA cm −2 , V oc = 1.16 V, and FF = 68.2% as compared to the experimental results (PCE = 2.34%, J sc = 7.64 mA cm −2 , V oc = 0.55 V and FF = 55.8%). However, W. Ke et al 64 demonstrated the higher performance of single-junction solar cells (PCE = 7.14%, J sc = 22.54 mA cm −2 , V oc = 0.48 V and FF = 65.9%) with 10% en-doping (1.5 eV) as compared to 25%.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…† First, the top cell was simulated by adopting the AM 1.5 spectrum with a conventional temperature of 300 K, known as a standalone condition, using drift-diffusion SCAPS-1D software. 60 The simulated solar cell showed an excellent PCE of 9.05% in combination with J sc = 11.42 mA cm −2 , V oc = 1.16 V, and FF = 68.2% as compared to the experimental results (PCE = 2.34%, J sc = 7.64 mA cm −2 , V oc = 0.55 V and FF = 55.8%). However, W. Ke et al 64 demonstrated the higher performance of single-junction solar cells (PCE = 7.14%, J sc = 22.54 mA cm −2 , V oc = 0.48 V and FF = 65.9%) with 10% en-doping (1.5 eV) as compared to 25%.…”
Section: Resultsmentioning
confidence: 67%
“…9 ). Similar to our previous publication, 60 the transmitted AM 1.5 spectrum by the top WBGC was calculated by employing the absorption coefficient and thickness of all layers present in the top cell (shown in Fig. 10a ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Also, the absorber thickness is more than the optimum value (400 nm for HTL‐free devices and 300 nm for MnS‐HTL devices), and the photogenerated charge carriers take a longer transfer path, which directs to higher recombination, detrimental to the device performance. [ 36–38 ] Overall, the annealed MnS‐HTL consisting of all Sb 2 (S,Se) 3 devices display higher PCE than HTL‐free and non‐annealed MnS‐HTL devices (see Figure 6b and Table S4–S6, Supporting Information). For example, annealed MnS‐HTL‐based device A exhibited an efficiency of 12.70%, which is higher than the non‐annealed device (12.05%) and HTL‐free device (11.03%), respectively.…”
Section: Resultsmentioning
confidence: 98%